The Value of Cerebral CT Angiography with Low Tube Voltage in Detection of Intracranial Aneurysms - Tang, Kun (Biomed Res Int, 2015)
Objective. The aim of this study is to investigate the value of cerebral CT angiography (CTA) with low tube voltage in detection of intracranial aneurysms. Materials and Methods. A total of 294 consecutive patients with spontaneous subarachnoid hemorrhage (SAH) were enrolled in this study and randomly assigned into conventional voltage CTA (C-CTA) group and low voltage CTA (L-CTA) group. The objective and subjective image qualities were analyzed and compared between C-CTA and L-CTA groups. With the results of 3D-DSA as “gold standard,” the sensitivity, specificity, and accuracy of C-CTA and L-CTA in diagnosis of aneurysms were calculated and compared with each other. Results. Compared with group C-CTA, the CT dose index volume (CTDIvol) of group L-CTA reduced by 35.65%. There were no significant differences between C-CTA and L-CTA groups regarding objective and subjective image qualities. The sensitivity, specificity, and accuracy of L-CTA in diagnosis of aneurysms were 95.16%, 99.72%, and 99.42%, respectively. There were no significant differences in sensitivity, specificity, and accuracy between the C-CTA and L-CTA groups. Conclusion. The value of cerebral CTA with 100 kV low tube voltage in detection of intracranial aneurysms is significant, and it should be recommended as a routine scan method.